VIth INTERNATIONAL SYMPOSIUM ON EDIBLE ALLIACEAE - A. F. Agafonov; T. P. Suprunova (Овощи России, 2012)
On May 21 - 24, 2012 the 6th International Symposium on Edible Alliaceae was held at Japan (Fukuoka). The symposium was devoted to innovation in agriculture and food science for edible Alliaceae crops. The symposium provided a leading opportunity for scientists, growers and market players from around the world to discuss and share information on genetics and breeding, cultivation, quality control and so on in bulb onion, garlic, and bunching onion.